From Lisbon to Macau: The conquest of the air as seen by the Portuguese press in a comparative approach - Costa, C. M.; Pestana, O. (Portuguese Journal of Social Science, 2020)
In 1924, two well-known Portuguese servicemen made the first flight between Lisbon and Macau. The press of the time not only followed this adventure but also supported it, playing an active role as it unfolded. This article presents a comparison of the content of news published in two Portuguese newspapers, the Diário de Lisboa and Comércio do Porto, one based in Lisbon and the other in Porto, between 1 April and 30 June that year, the period during which the trip took place. The aim is to analyse the involvement of these periodicals in this project, which assumes journalistic characteristics, but also their commitment to raise funds and their role in the mobilization of the public and as intermediaries between the pilots and public authorities.